Infrastructure quality and sense of campus community in public Universities in Uganda - Samuel Lukenge; Wilson Mugizi; Mathias Kiryowa (International Journal of Educational Policy Research and Review, 2026)
Infrastructure quality is widely recognised as an important factor shaping students’ academic and social experiences in higher education, as it influences the physical and technological environment within which learning and interaction take place. This study examined the influence of infrastructure quality on students’ sense of campus community in public universities in Uganda. Specifically, the study investigated the extent to which lecture room quality, extramural facilities, utilities, and information and communication technology (ICT) predict students’ sense of campus community. Guided by the Psychological Sense of Community Theory, the study employed a quantitative correlational research design. Data were collected using a structured self-administered questionnaire from 393 undergraduate students, predominantly in their final year, selected from a population of 11,913 students in the Faculties of Science and Schools of Education across four public universities. The findings revealed that students perceived both infrastructure quality and their sense of campus community to be at moderate levels. Correlation analysis showed positive relationships between all dimensions of infrastructure quality and students’ sense of campus community. Regression analysis further indicated that lecture room quality, utilities, and ICT significantly predicted students’ sense of campus community, while extramural facilities, although positively related, did not have a statistically significant effect. The study concludes that enhancing the quality of lecture rooms, utilities, and ICT infrastructure is important for fostering a stronger sense of campus community among students in public universities